Instrumental measurent of the texture of hard-boiled egg yolks enriched with different levels of conjugated linoleic acid - Diezma Iglesias, B.=700 1 Garcia Rebollar, P.; Ruiz Altisent, M.; Alvarez Carro, C.
(En, Es)
Ilus., 20 ref.
Keywords: HUEVOS; CARACTERISTICAS DEL HUEVO; YEMA DE HUEVO; CALIDAD; PROPIEDADES ORGANOLEPTICAS; COMPOSICION QUIMICA; ACIDOS GRASOS; ENSAYO; PRENSADO; FIRMEZA; TEXTURA; ESPAÑA; ENSAYO DE COMPRESION; HUEVOS COCIDOS